“KULAK NEMPIL” IN THE METHOD OF DETERMINING THE SELL PRICE CRACKERS RAW BLITAR MARKET - Irma Ayu Rahmawati; Diana Elvianita Martanti (JOSAR (Journal of Students Academic Research), 2020)
This research was conducted at the Raw Crackers Shop in Legi Market on March 1, 2019 to May 31, 2019. This study aims to analyze the crackers method and determine the selling price of the crackers. The research method used is descriptive qualitative method. The results of this research are traders to get goods when the stock of goods in the warehouse from the producers runs out, namely the kulak method. Kulakan that is applied is "kulak nempil". The selling price is determined by following the price obtained from nempil with the difference between Rp. 1000.00 to Rp. 2000.00 from the nempil kulak at the market selling price, if the nempil price is high the selling price is higher and if the nempil price is low then the selling price follows the market price. The payment method for the kulak nempil transaction is cash on hand at the kulak price based on the agreement of the bargaining